D-dimer in suspected pulmonary embolism - Giannitsis, Evangelos; Mills, Nicholas; Müller, Christian (European heart journal - acute cardiovascular care, 2023)
D-Dimers are formed after degradation of cross-linked fibrin by plasmin.1 Thus, D-dimers indicate the presence of intravascular clot formation and reflect the early process of fibrinolysis. Therefore, D-dimers play an important role for the diagnosis of venous thromboembolism (VTE). Given that D-dimer elevations are not specific to clot formation but may also be encountered after infections or miscellaneous inflammatory processes, the major indication of D-dimers is traditionally to rule out and not to rule in VTE.1,2D-Dimers should be measured after a thorough clinical evaluation and anamnesis as the decision to measure D-dimer should be restricted to those without potential confounders and a low or low-to-intermediate clinical pre-test probability.2 The latter should be assessed as a gatekeeper before ordering a D-dimer test (Central Illustration) in outpatients using established validated scores such as the Wells or Geneva score, but also using gestalt of an experienced physician.3 Another validated strategy that considers clinical pre-test probability utilizes three items from the Wells score, namely signs of deep venous thrombosis, haemoptysis, and pulmonary embolism (PE) more likely than an alternative diagnosis together with two different D-dimer thresholds.2 Pulmonary embolism is considered to be excluded in patients without clinical items and D-dimer levels < 1000 ng/mL or in patients with one or more clinical items and D-dimer levels < 500 ng/mL.